Rethinking the Lintnerian Linear Valuation Model - Shih-Cheng Lee; Jiun-Lin Chen; Shu-Chen Lu; Lei Xu (Australasian Accounting, Business and Finance Journal, 2014)
This paper develops and tests a new valuation model. Callen and Morel (2000) apply the Lintner (1956) dividend model to the famous Ohlson (1995) valuation model and develop the Lintnerian linear accounting valuation model (henceforth, the CM model). However, Bauer and Bhattacharyya (2007) suggest that the Lintner dividend model does not fit firm dividend policy behaviour appropriately and decide to construct another dividend policy process. This study applies their dividend model to construct a new valuation model, which performs better than the original Ohlson and CM models empirically. Applying the Engle and Granger (1987) cointegration concepts, we examine the performance of the three models for the 1,564 firm-year panel data of US companies from 1973 to 2006. Our findings indicate that all tested variables are stationary after the first order difference process and that all three models exhibit long-run equilibrium relations among equity price and explanatory variables. However, our model has the highest cointegration ratio, which is almost 100 percent of sample firms. Hence, our model is more suitable to evaluate the equity value and provides improvement for the previous accounting valuation models.
Keywords: Ohlson Model; Lintner Model; ADF Test; Engle and Granger Test